FACTORS INFLUENCING THE ADOPTION OF IMPROVED GROUNDNUT VARIETIES (IGVs) OF N2AFRICA PROJECT AMONG FARMERS IN BORNO STATE, NIGERIA - Kadafur, I. M.; Garba, M.; Abdullahi, S.; Abu, I. A.; Abubakar, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the adoption of improved groundnut varieties (IGVs) in N2Africa project among farmers in Borno State, Nigeria. A multi stage sampling techniques was used in selecting 600 respondents. Data were collected using structured questionnaires and were analysed using descriptive and inferential statistics. The results reveal that majority (75.0%) of the respondents were male and 28.2% had secondary education with more than half (53.7%) being members of cooperatives. The respondents had an average age, household size and farming experience of 45 years, 8 persons and of 22 years respectively. Almost all (96.5%) of the respondents were aware of the IGVs. The major sources of information on IGVs were extension agents (89.5%), radio (88.3%), farmer groups (70.8%) and friends/fellow farmers (62.7%). The results of logit regression analysis revealed that membership association (P< 0.05), farm size P< 0.01) and sex (P< 0.1) significantly influenced the adoption of IGVs. The major constraints to the adoption of IGVs were high cost of improved groundnut varieties (98.2%), scarcity of the IGVs (94.8%), and inadequate capital (94.3%). The study concluded that adoption of IGVs was high in the study area and SAMNUT22 had the highest adoption rate. The study also concluded that sex, group membership and farm size were the factors affecting the likelihood of adoption of IGVs with sex and participation determining the intensity of adoption. In addition, the adoption of IGVs had improved groundnut farmers’ productivity, income and expenditure. It is recommended that community seed production, farmer participation should be encouraged and promoted to facilitate easy access to IGVs by farmers, private sectors should be encouraged to invest in extension services and farmers should be encouraged to participate in savings and internal lending community in order to raise more capital and enjoy economy of scale.